PENGARUH KEPATUHAN WAJIB PAJAK TERHADAP KINERJA PENERIMAAN PAJAK DI KPP PRATAMA MAKASSAR BARAT - Muhammad Adil (LP3M Universitas Muhammadiyah Makassar)
This study was conducted with the aim to Analyze the influence of taxpayer compliance on the performance of tax revenue. This study uses primary and secondary data, primary data obtained through Questionnaires from taxpayer KPP Pratama West Makassar as much as 100 people taxpayers from the total number of taxpayers KPP West Makassar as many as 58,191 people. Data were analyzed using Statistical Product and Service Solutions (SPSS) program. The results of this study indicate that taxpayer compliance has a positive and significant impact on the performance of tax revenue in KPP Pratama West Makassar.